e(x+7)=26

Simple and best practice solution for e(x+7)=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for e(x+7)=26 equation:


Simplifying
e(x + 7) = 26

Reorder the terms:
e(7 + x) = 26
(7 * e + x * e) = 26
(7e + ex) = 26

Solving
7e + ex = 26

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Reorder the terms:
-26 + 7e + ex = 26 + -26

Combine like terms: 26 + -26 = 0
-26 + 7e + ex = 0

The solution to this equation could not be determined.

See similar equations:

| -3+6+2g=45 | | 6ln(6p)=12 | | 5/100=8.38/x | | -4(-4+5x)=36 | | x^2-16=-63 | | (X+4)(x+3)=25 | | 2x-6=-6x+90 | | -27/-3 | | 0,9x-7,4=-0,4x+4,3 | | -3x-6=-6+3x | | 2e^5*x=9 | | 5x+2yi=-15+8i | | 2+86=180 | | 2x-5/-3=11 | | -143=14k | | 2e^5x=9 | | 7x-3=78-2x | | 7-3x/4=34 | | 2x-2=22-4x | | 8x^2-23x-36=0 | | ln(a-10)-1=0 | | 5x+10-x=10 | | 7-3x=6x-56 | | 4(4x+1)=4x-7x | | 13/3x-2=4/x | | x^4+5*x^3+9*x^2+8*x+4=0 | | 3-7x+2x=-37 | | 9x-26=30-5x | | 12t^2-5t+6=8 | | ln(p+10)=1 | | 8w+8=16 | | -9y+9=72 |

Equations solver categories